The wild boar Sus scrofa as a threat to ground‐nesting bird species: an artificial nest experiment. (29th April 2021) - Mori, E.; Lazzeri, L.; Ferretti, F.; Gordigiani, L.; Rubolini, D.
Abstract: Nest predation is reported as a cause of reproductive failure of ground‐nesting bird species whose populations in Europe are declining. Conversely, European populations of the wild boar Sus scrofa have been expanding, leading to increasing threats to habitats and ecological communities. The impacts of wild boar on ground‐nesting bird species are poorly known and have never been explicitly assessed. We conducted an artificial ground‐nest experiment in Mediterranean habitats of central Italy using camera traps to assess predator identities. Deployed nests contained quail or chicken eggs, and predation occurred within one week for 47/48 deployments carried out during March‐July 2020. The wild boar was the most common predator (36% deployments), followed by the magpie Pica pica (18%), the red fox Vulpes vulpes (10%) and the pine marten Martes martes (10%). Predation by other species was occasionally observed. Egg type and deployment habitat did not significantly influence time to predation or the likelihood that a nest was preyed upon by wild boar, respectively. The presence of a stuffed gull close to the nests significantly delayed predation. Nests preyed by birds and mammals other than wild boar were often subsequently scavenged by wild boar, which consumed the remaining eggs or eggshells. Time to predation increased from spring to summer, suggesting a reduction of predation intensity during periods when the availability of natural eggs is lowest. The likelihood of a nest being preyed upon by the wild boar compared to other predators increased when wild boar frequency of occurrence in 1‐week camera trap shootings was the highest, suggesting that higher abundance/activity of this species triggered increased egg predation. The wild boar might act as major predators of ground‐nesting bird species in Mediterranean habitats and the large‐scale population increase of this ungulate should be considered a significant threat to ground‐nesting species of European conservation concern. Abstract : We found that the wild boar was the most common predator of ground nests in Central Italy, followed by the magpie, the red fox and the pine marten. Nests preyed by birds and mammals other than wild boar were often subsequently scavenged by wild boar which consumed the remaining eggs or eggshells. The wild boar might act as a major predator of ground‐nesting bird species in Mediterranean habitats and the large‐scale population increase of this ungulate should be considered a significant threat to ground‐nesting birds of European conservation concern.